Assessing ethical behavior and self-control in elite ultimate championships: a cross-sectional study using the spirit of the game scoring system - José Pedro Amoroso; José Pedro Amoroso; Luís Coelho; Luís Coelho; Luís Coelho; Rebecca A. Boulton; Christie M. González-Toro; Felipe Costa; Efstathios Christodoulides; Wouter Cools; Wouter Cools; Dean Dudley; et al. (Frontiers Media S.A., 2024)
IntroductionImplementing a self-refereeing system presents a unique challenge in sports education, particularly in academic and training settings where officiated sports prevail. However, Ultimate Frisbee stands out by entrusting players with both athlete and referee roles, introducing distinctive ethical complexities. This manuscript is intended to evaluate ethical behavior and self-control within the Spirit of the Game (SOTG) scoring system in Elite Ultimate. To address these, Ultimate employs the (SOTG) scoring system, integral since the sport's inception in the late 1980s. SOTG aims to enhance and evaluate athletes' ethical conduct. This study evaluates SOTG's effectiveness in elite-level Ultimate, analyzing variations across divisions and age groups in three high-level tournaments.MethodsUsing a cross-sectional design, data were collected from five international Ultimate tournaments in 2022. Teams spanned diverse age groups (under 17 to over 50) and divisions (women's, mixed, open). Post-match, teams assessed opponents' SOTG in five domains: Rules knowledge, fouls, fairness, attitude/self-control, and communication. Ratings used a 5-point Likert scale ("poor" to "excellent"). An overall SOTG score was calculated by aggregating domain scores.ResultsOur study consistently revealed high SOTG scores, reflecting strong sportsmanship. "Positive attitude and self-control" consistently ranked highest, while "Knowledge and use of the rules" scored lowest. Divisional differences in SOTG were statistically insignificant. Notably, WMUCC2022 (participants aged 30+) had significantly higher SOTG scores, possibly indicating age-related self-control improvement or evolving sport culture. Lower rules knowledge scores may stem from linguistic translation challenges.ConclusionSelf-refereeing promotes ethical behavior across divisions and age groups. SOTG underscores sportsmanship's importance and aligns with International Olympic Committee (IOC) and with Sustainable Development Goals (SDGs), particularly SDG 3, 4, 5 and 16 fostering a fairer, healthier, and more peaceful world.